Effects of migration on tuberculosis epidemiological indicators in low and medium tuberculosis incidence countries: A systematic review - Sarah Jackson; Zubair Kabir; Catherine Comiskey (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2021)
Background: Tuberculosis (TB) remains one of the top ten causes of death each year globally. While the risk of migrant TB is linked to the TB incidence in their country of origin, the migration process can increase the TB risk. Objective: We aimed to synthesis the evidence on key differences in the epidemiological profile of TB between migrants from high TB incidence birth countries and non-migrants resident in low to medium incidence TB countries. Methods: We conducted a systematic review where the population was all active TB cases in countries with low to medium TB incidence (<40/100,000 population), the exposure was migration to a low or medium TB incidence country and the comparator was non-migrant TB cases in low or medium incidence countries. Overall proportions were compared between migrants and non-migrants, using Fisher’s exact test. Meta-analysis of proportions was carried out for the primary outcome (active TB) while meta-analyses of odds ratios (ORs) were performed using a random effects model for secondary outcomes; sputum-smear positivity, any first line drug resistance, multi-drug resistance (MDR), clustered cases, HIV coinfections and successful treatment. Heterogeneity was evaluated and sources were investigated using subgroup and sensitivity analysis. Results: Significant differences were found in the overall proportions of high TB incidence migrants and non-migrants for MDR cases, clustered cases, HIV coinfections and successful treatment, as well as a significant difference in the OR among MDR cases (3.91). Conclusion: This review has demonstrated significant differences in key epidemiological indicators between high TB incidence migrants and non-migrants, indicating policy implications.